Rapid Detection of Brucella spp. and Elimination of Carryover Using Multiple Cross Displacement Amplification Coupled With Nanoparticles-Based Lateral Flow Biosensor - Li, Shijun; Liu, Ying; Wang, Yue; Wang, Ming; Liu, Chunting; Wang, Yi (Frontiers in Cellular and Infection Microbiology, 2019)
Brucella spp. is capable of causing disease in a range of animal hosts, and human brucellosis is regarded as a life-threating disease. A novel isothermal amplification technique, termed multiple cross displacement amplification (MCDA), was employed for detecting all Brucella species strains. Brucella-MCDA targets the Bscp31 gene (Brucella species-specific gene) to specifically design a set of ten primers. The Brucella-MCDA can be coupled with nanoparticles-based lateral flow biosensor (LFB) for highly specific, simple, rapid and visual detection of Brucella-specific amplicons. Using the protocol, a MCDA amplification followed by 2-min LFB resulted in visualization of DNA products trapped at the LFB test line. Various species of Gram-positive and Gram-negative strains are applied for optimizing and evaluating the target assay. Optimal MCDA condition is found to be 63°C for 40 min, with detection limits at 10 fg of templates in the pure cultures. The specificity of MCDA-LFB technique is of 100%, and no cross-reactions to non-Brucella strains are observed according to the specificity examination. Furthermore, dUTP and AUDG enzyme are added into the MCDA reaction mixtures, which are used for removing false-positive amplification generating from carryover contamination. Thus, 20 min for rapid template extraction followed by AUDG digestion (5 min), MCDA (40 min) combined with LFB detection (2 min) resulted in a total assay time of approximately 70 min. In sum, Brucella-MCDA-LFB technique is a rapid, simple, reliable and sensitive method to detect all Brucella species strains, and can be used as potential screening tool for Brucella strains in various laboratories.